2017
DOI: 10.7600/jpfsm.7.35
|View full text |Cite
|
Sign up to set email alerts
|

No association between passive material property and cross-sectional area in human hamstring

Abstract: The passive material properties of a muscle, as evaluated by shear or Young's modulus, can vary depending on the muscle cross-sectional area (CSA), since intramuscular compositions such as adipose tissue and connective tissue change with muscle hypertrophy and atrophy. However, the relationship remains unclear between the passive material properties and CSA of a muscle. Therefore, we examined whether passive muscle shear modulus is related to muscle CSA in the human hamstring. The shear modulus and anatomical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 23 publications
(33 reference statements)
0
4
0
Order By: Relevance
“…Recently, Miyamoto et al examined whether passive muscle shear modulus is related to muscle cross-sectional area in the hamstrings. As a result, they suggested that there were no significant correlations between shear modulus and cross-sectional area in each or overall hamstrings 13 . On the other hand, it is reported that the fascicle length is shorter in the SM (5.43±0.87 cm) and BF-lh (7.02±1.28 cm) than in the ST (14.87±3.52 cm) 18 .…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Miyamoto et al examined whether passive muscle shear modulus is related to muscle cross-sectional area in the hamstrings. As a result, they suggested that there were no significant correlations between shear modulus and cross-sectional area in each or overall hamstrings 13 . On the other hand, it is reported that the fascicle length is shorter in the SM (5.43±0.87 cm) and BF-lh (7.02±1.28 cm) than in the ST (14.87±3.52 cm) 18 .…”
Section: Discussionmentioning
confidence: 99%
“…13,14 Contradictory findings have been reported regarding the shear modulus of the hamstring in passively lengthened positions. Hirata et al 7 and Miyamoto et al 9 showed that, among the hamstring muscles, SM had the highest shear modulus, whereas Le Sant et al 8 reported that the BFlh had the highest shear modulus although the testing posture was similar (ie supine) in the Hirata et al's and Le Sant et al's studies. These contradictions may be due to different measurement sites for muscle shear modulus.…”
Section: Introductionmentioning
confidence: 97%
“…Ultrasound shear wave elastography (SWE) has been used to quantify localized shear modulus (a measure of stiffness, expressed in the unit of Pascal) of individual muscles, 1,[7][8][9][10][11][12] based on the propagation speed of remotely induced shear waves. 13,14 Contradictory findings have been reported regarding the shear modulus of the hamstring in passively lengthened positions.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation